REPLY TO THE COMMENT BY A. RODRÍGUEZ RAMÍREZ ON “THE GEOLOGICAL RECORD OF THE OLDEST HISTORICAL TSUNAMIS IN SOUTHWESTERN SPAIN” BY FRANCISCO RUIZ, MANUEL ABAD, JOAQUÍN RODRÍGUEZ VIDAL, LUIS MIGUEL CÁCERES, MARÍA LUZ GONZÁLEZ-REGALADO, MARÍA ISABEL CARRETERO, MANUEL POZO & FRANCISCO GÓMEZ TOSCANO, PUBLISHED IN RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 114(1): 147-156 (2008) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
These reply comments were focused on the different affirmations made by Rodríguez Ramírez (2008, this volume) about our previous paper.